STRATEGI PENINGKATAN PENANAMAN MODAL ASING MELALUI LAYANAN HUKUM OLEH CLEON BUSINESS CONSULTING: STRATEGY TO INCREASE FOREIGN INVESTMENT THROUGH LEGAL SERVICES BY CLEON BUSINESS CONSULTING - Eka Putri Febrianti; I Wayan Joniarta (LPPM Universitas Abdurrab, 2024)
The rapid development of technology has made capital market movements more widespread, reaching across countries. Such as foreign investment activities, as funds from abroad, its role is very important for developing countries such as Indonesia. In practice, foreign investors use legal services and legal assistance obtained from advocates or offices that provide legal services, such as Cleon Businnes Consulting. As well as where the author carries out Field Work Practices (PKL). So this paper aims to overcome legal problems, especially in foreign investment activities. To support the process of writing this article, the author conducted a service as well as observations regarding the legal services provided by Cleon Business. So that this service is presented with the title â€œStrategy for Increasing Foreign Investment Through Legal Services by Cleon Business Consultingâ€. The method the author uses is the interview method with the company, so as to produce actual writing. The conclusion obtained in writing this article is that Cleon Business Consulting as Legal Consulting plays a crucial role in providing the services needed to ensure legal compliance and investment sustainability. Cleon Business Consulting provides 4 (four) legal services namely: 1) Pre Investment (legal services before the investment is made); 2) Invest and company establishment (investment and company establishment); 3) Company legal compliance (choosing the right legal entity for the company based on Indonesian law); 4) transaction handling (handling or handling all existing transactions). While the obstacles faced by Cleon Business Consulting while providing these legal services are: 1) related to the understanding of clients who are foreign nationals; 2) limited knowledge of the various stakeholders (shareholders) involved; 3) regulatory restrictions on the intentions of client needs.